1997
DOI: 10.1029/97ja01800
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of oxygen in aurora: Evidence for a local mechanism

Abstract: Abstract. A ground-based and rocket investigation of the response of the neutral atmosphere to E region auroral heating has been carried out at Poker Flat, Alaska. The temporal evolution of the atomic oxygen to molecular nitrogen ratio (O/N2) in the lower thermosphere has been monitored using the optical emissions from the aurora as a diagnostic. Comparisons between the changes in the O/N 2 ratio and the auroral Joule and particle heating have shown several examples of close similarity between the durations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 15 publications
5
37
0
Order By: Relevance
“…This is qualitatively consistent with models that have been developed for many years. The magnitude of the observed decrease is also consistent with previous observations recently reported by Christensen et al [1997], where it was concluded that local dynamical mechanisn•s a.re causing the composition change. However, in that paper it was asserted that recent three-dimensional numerical models [Sun et al, 1995] significantly •lnderpredicted the magnitude of the observed decrease in O/N2.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is qualitatively consistent with models that have been developed for many years. The magnitude of the observed decrease is also consistent with previous observations recently reported by Christensen et al [1997], where it was concluded that local dynamical mechanisn•s a.re causing the composition change. However, in that paper it was asserted that recent three-dimensional numerical models [Sun et al, 1995] significantly •lnderpredicted the magnitude of the observed decrease in O/N2.…”
Section: Discussionsupporting
confidence: 82%
“…However, in that paper it was asserted that recent three-dimensional numerical models [Sun et al, 1995] significantly •lnderpredicted the magnitude of the observed decrease in O/N2. In contrast to the events considered by Christensen et al [1997] where the dominant heat source was Joule dissipation, in this work the majority of the total hea,ting was due to particle precipitation. Whether or not this is an important difference will require additional model analysis.…”
Section: Discussionmentioning
confidence: 61%
“…Energetic particle precipitating and Joule heating due to dissipation of electric currents will heat the lower thermosphere during aurora and drive vertical and horizontal transport of the atmospheric gases (Fuller-Rowell, 1985). In general, heating and O/N 2 ratio are anti-correlated; the ratio O/N 2 in the lower thermosphere (E-region) is at a minimum during maximum particle and Joule heating (Hecht et al, 1995;Christensen et al, 1997). Thus, both heating and atmospheric composition will influence the optical brightness ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Any local signatures of composition change are masked in such cases. Christensen et al [1997] presented data that indicated that during some substorms, decreases in the O/N 2 density ratio of the lower E region of up to 50% occurred in a period of a few tens of minutes after the peak of local auroral energy deposition. These timescales suggested that the mechanisms that drive these changes were located not too far distant from the observation site.…”
Section: Introductionmentioning
confidence: 99%